(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
A nearly complete but disarticulated skeleton of a small sized nothosaur is described. The specimen was collected in 2003 from an outcrop of the Besano Formation (Grenzbitumenzone of Swiss authors) of latest Anisian (Middle Triassic) age, in the Monte San Giorgio Area, northern Italy. The osteology of the postcranial skeleton supports the assignment to the genus Nothosaurus, and also excludes its belonging to Nothosaurus giganteus/Paranothosaurus amsleri already known from coeval localities of the Besano Formation in the Swiss part of the Monte San Giorgio area. Despite the lack of most of the skull, which contains diagnostic characters at the species level for Nothosaurus, the few preserved cranial elements suggest similarities with N. juvenilis which skull, and only known part, is also of comparable size. This specimen is particularly significant because it improves the knowledge of the osteology of N. juvenilis and because the second Nothosaurus species, smaller than N. giganteus/P. amsleri, suggests coexistence of sympatric species characterized by size and, probably, trophic differentiation within the genus Nothosaurus in the Monte San Giorgio area as occurred in the coeval Germanic Basin.